Food allergen control: Tropomyosin analysis through electrochemical immunosensing. (1st December 2022) - Torre, Ricarda; Freitas, Maria; Costa‐Rama, Estefanía; Nouws, Henri P.A.; Delerue‐Matos, Cristina
Graphical abstract: Highlights: Tracking crustacean-containing food can prevent severe allergic reactions. A simple and selective electrochemical immunoassay was developed for tropomyosin. A low linear range between 2.5 and 20 ng mL −1 was achieved. The results of tropomyosin analysis in food products were validated. Abstract: Regulations of the EU obliges the indication of the presence of allergens on food labels. This work reports the development of an electrochemical immunosensor to determine tropomyosin (TPM) – a major shellfish allergen – prevailing in the muscles of crustacean species. Two linear ranges between the signal and TPM concentration were obtained: between 2.5 and 20 ng mL −1 and between 30 and 200 ng mL −1, with a lowest limit of detection of 0.47 ng mL −1 . The selectivity of the optimized immunoassay, tested with other food allergens (e.g., Cyp c 1, a fish allergen), assures the effective detection of TPM, enabling successful control of foodstuff labelling. Several (12) foods, containing high and low TPM concentrations and TPM-free samples, were analysed using the sensor. A conventional ELISA kit and recovery assays were used to evaluate the accuracy of the results.